Simultaneous immobilization of heavy metals and nutrient elements in contaminated sediment using a novel composite agent product - Xiaori Fu; Peishu Huo; Wenji Wang; Dexiao Li; Xiaojing Liu; Guilu Zeng; Shuguang Lyu (Water Science and Technology, 2023)
In this research, an innovative type of sediment resource treatment agent (SRA) was synthesized successfully, which could immobilize ammonia nitrogen (NH3-N), total phosphorus (TP), potassium (K), and simultaneously stabilize cadmium (Cd), lead (Pb), chromium (Cr), copper (Cu), nickel (Ni), and zinc (Zn) in dredged sediment. The effects of SRA dosage on stabilizing the nutrient elements and heavy metals were investigated. The results demonstrated that the increase of SRA dosage significantly enhanced the stabilization of nutrients and heavy metals. The 14-day rainwater infiltration and rainwater scouring experiments were carried out. With the simulation test of rainwater infiltration, the stabilization ratios of Cr, Cu, Ni, Pb, Zn, Cd, NH3-N, TP, and K with 2% SRA addition reached 80.8%, 76.8%, 80.3%, 77.5%, 78.0%, 72.7%, 64.3%, 73.9%, and 73.9%, respectively. Under the action of rainwater scouring, the stabilization ratios of Cr, Cu, Ni, Pb, Zn, Cd, NH3-N, TP, and K with 6.4% SRA addition reached 84.6%, 84.0%, 77.6%, 87.3%, 80.0%, 61.5%, 76.2%, 77.8%, and 91.7%, respectively. Therefore, the results demonstrate that SRA is an excellent composite material in stabilizing heavy metals while reserving the nutrients in dredged sediment, thus showing great potential in the application for dredged sediment resource treatment. HIGHLIGHTS Stabilized heavy metals and nutrient elements were achieved simultaneously.; The stabilization under various test conditions was demonstrated.; The influence of SRA on sediment pH was investigated.; SRA could change the anaerobic environment of dredged sediment by releasing oxygen.; The stabilizing mechanisms on contaminants were elucidated.;